PAJAK PENGHASILAN TERHADAP TENAGA KERJA ASING SEBAGAI SUBYEK HUKUM PAJAK - Ramadhan, Hendy (Media Iuris, 2018)
Foreign workers who work in Indonesia, have rights and obligations that are governed by the laws and regulations applicable in Indonesia, including rules relating to taxation. The foreign workers residing in Indonesia may be subject to tax laws in Indonesia. For the implementatio of legal order in the field of taxation, there is a need to apply the law of income tax on foreign workers who work in Indonesia. This paper discusses the legal basis for the imposition of foreign workers income tax in Indonesia as well as the form of liability for violations of income tax regulation on foreign workers in Indonesia. Based on this paper, foreign worker is one of the subject of income tax in Indonesia and can be subject to domestic tax or foreign tax subject depending on how long they have worked in Indonesia. Whereas in the event of any fraud related to the income tax on foreign worker, in the case the tax deduction is done by the company where the foreign worker is working, then the sanction given to the party who withholds the income tax.